Implementasi Manajemen Risiko Sistem Administrasi Layanan Akademik Menggunakan Framework COBIT 5.0 - Furiansyah Dipraja; Rifqi Syamsul Fuadi; Tonton Taufik Rachman (INTERNAL (Information System Journal), 2021)
The importance of the academic service administration system in supporting the academic service process and data management, makes it a vital system that must be avoided from risks that can hinder and affect technology-based systems. Data processing and academic services in Higher Education must be carried out optimally and integrated, because it is very necessary to realize quality services. To minimize the impact of risk, the authors make policies regarding risk management including managing risk profiles. To find out the achievement of information technology risk management implementation, the authors evaluate using the COBIT 5 framework in the APO12 (Manage Risk) process domain. Based on the results of the evaluation of the data obtained through the distribution of questionnaires, interviews and observations, it was found that the capability level and APO12 domain values ??were at level 1. thus resulting in a gap of 2 levels. The process of evaluating the application of information technology risk management in the system using the COBIT 5 framework, especially the APO12 (Manage Risk) process domain, obtained a level 2 capability level, namely performed process, which means that every process implemented has achieved the specified goals.